2018
DOI: 10.1037/pas0000526
|View full text |Cite|
|
Sign up to set email alerts
|

Complementary exploratory and confirmatory factor analyses of the French WISC–V: Analyses based on the standardization sample.

Abstract: Interpretation of the French Wechsler Intelligence Scale for Children-Fifth Edition (French WISC-V; Wechsler, 2016a) is based on a 5-factor model including Verbal Comprehension (VC), Visual Spatial (VS), Fluid Reasoning (FR), Working Memory (WM), and Processing Speed (PS). Evidence for the French WISC-V factorial structure was established exclusively through confirmatory factor analyses (CFAs). However, as recommended by Carroll (1995); Reise (2012), and Brown (2015), factorial structure should derive from bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
42
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 72 publications
22
42
1
Order By: Relevance
“…Omega‐hierarchical (ω H ) coefficients (McDonald, ) ranged from .817 (Canivez et al ., , ) to .847 (Canivez et al ., ; Dombrowski, Canivez, et al ., ) for the general factor but omega‐hierarchical subscale (ω HS ) coefficients for the four WISC‐V group factors ranged from .131 to .530. Similar reliability estimates were found with the French WISC‐V (Lecerf & Canivez, ). Thus, independent EFA results have suggested that a four‐factor solution appears to be the best measurement model for the WISC‐V.…”
Section: Introductionsupporting
confidence: 80%
See 4 more Smart Citations
“…Omega‐hierarchical (ω H ) coefficients (McDonald, ) ranged from .817 (Canivez et al ., , ) to .847 (Canivez et al ., ; Dombrowski, Canivez, et al ., ) for the general factor but omega‐hierarchical subscale (ω HS ) coefficients for the four WISC‐V group factors ranged from .131 to .530. Similar reliability estimates were found with the French WISC‐V (Lecerf & Canivez, ). Thus, independent EFA results have suggested that a four‐factor solution appears to be the best measurement model for the WISC‐V.…”
Section: Introductionsupporting
confidence: 80%
“…In contrast, four robust factors with theoretically consistent subtest associations resembling the traditional Wechsler structure emerged from the EFA. The present results replicated the outcomes of EFA studies of the WISC‐V in the United States and in other countries in regard to the inadequate fifth factor (Canivez et al ., , ; Dombrowski, Canivez, Watkins, & Beaujean, ; Dombrowski, Canivez, et al ., ; Lecerf & Canivez, ). Of interest, the AR subtest was the sole salient loading on the fifth factor in the French standardization sample but FW, MR, and VP subtests were singlets in the US sample depending on examinee age.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations